Social science methodology : a unified framework - Gerring, John, 1962- (Cambridge : Cambridge University Press, 2012)
John Gerring's exceptional textbook has been thoroughly revised in this second edition. It offers a one-volume introduction to social science methodology relevant to the disciplines of anthropology, economics, history, political science, psychology and sociology. This new edition has been extensively developed with the introduction of new material and a thorough treatment of essential elements such as conceptualization, measurement, causality and research design. It is written for students, long-time practitioners and methodologists and covers both qualitative and quantitative methods. It synthesizes the vast and diverse field of methodology in a way that is clear, concise and comprehensive. While offering a handy overview of the subject, the book is also an argument about how we should conceptualize methodological problems. Thinking about methodology through this lens provides a new framework for understanding work in the social sciences.
Preface -- 1. A unified framework -- Part I. General: 2. Beginnings -- 3. Arguments -- 4. Analyses -- Part II. Description: 5. Concepts -- 6. Descriptive arguments -- 7. Measurements -- Part III. Causation: 8. Causal arguments -- 9. Causal analyses -- 10. Causal strategies: X and Y -- 11. Causal strategies: beyond X and Y -- 12. Varying approaches to causal inference -- Part IV. Conclusions: 13. Unity and plurality -- 14. Setting standards -- Postscript: justifications -- Appendix: a few words on style.
Title from publisher's bibliographic system (viewed on 18 Jul 2016).
Keywords: elektronické knihy; electronic books; Social sciences -- Methodology